2013
DOI: 10.1371/journal.pcbi.1003271
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Change of Global and Local Information Processing in Propofol-Induced Loss and Recovery of Consciousness

Abstract: Whether unique to humans or not, consciousness is a central aspect of our experience of the world. The neural fingerprint of this experience, however, remains one of the least understood aspects of the human brain. In this paper we employ graph-theoretic measures and support vector machine classification to assess, in 12 healthy volunteers, the dynamic reconfiguration of functional connectivity during wakefulness, propofol-induced sedation and loss of consciousness, and the recovery of wakefulness. Our main fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
119
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 97 publications
(191 reference statements)
22
119
1
Order By: Relevance
“…In particular, the changes in non-specific thalamo-cortical connections seem to correlate with an altered state of consciousness. However, another study found that propofol preferably suppresses cortico-cortical connections [51], which is consistent with the present findings (Figs 3 and 4) of well preserved thalamo-cortical flow at UNRES within the pathways for auditory information processing. Thus, the primary site for the hypnotic effects of propofol seems to be the cerebral cortex followed by the suppression of deeper structures with higher doses [52].…”
supporting
confidence: 93%
“…In particular, the changes in non-specific thalamo-cortical connections seem to correlate with an altered state of consciousness. However, another study found that propofol preferably suppresses cortico-cortical connections [51], which is consistent with the present findings (Figs 3 and 4) of well preserved thalamo-cortical flow at UNRES within the pathways for auditory information processing. Thus, the primary site for the hypnotic effects of propofol seems to be the cerebral cortex followed by the suppression of deeper structures with higher doses [52].…”
supporting
confidence: 93%
“…Furthermore, changes in thalamocortical connectivity have also been shown to underlie the dynamic reconfiguration of brain networks during loss of consciousness by anesthetic agent. 38 While we stress that because of the low sample the results should not be generalized beyond our cohort, these findings are consistent with the idea that functional or structural impairment (which we cannot distinguish in our dataset) within a cortico-striatopallidal-thalamo-cortical mesocircuit is characteristic of severe DOC. 23,35 In this work, we have shown that several levels of cognitive processing, including the ability to comprehend verbal information, maintain information through time, and adopt voluntary mindsets-a set of high-level cognitive processes thought to be crucial for consciousness 39 -can be maintained in patients with DOC.…”
supporting
confidence: 82%
“…28 On the one hand, the negative association between motor/communication scores and atrophy along the anterior and dorsomedial regions of thalamus is consistent with the mesocircuit theory according to which corticopetal projections from thalamus to prefrontal cortex are crucial for sustaining organized behavior 26 and integrating information across different regions of cortex. 29 These regions are known to be a target of secondary, nonmechanic, damage (eg, Wallerian degeneration) in acute moderate-to-severe brain injury, with the degree of atrophy correlating with long-term outcome. 10 Furthermore, the dorsomedial aspect of thalamus is known to be the main subcortical structure projecting to prefrontal cortex, 30 and to play a key role in the regulation of higher cognitive functions in DOC patients.…”
Section: Discussionmentioning
confidence: 99%